2018
DOI: 10.1002/adom.201800462
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Field Enhancement of TiO2 Porous Layer up to 500‐Fold

Abstract: Surface Enhanced FluorescenceWhen a noble metal with nanostructure is irradiated with light, localized surface plasmons are resonantly generated, i.e., "plasmon resonance" occurs, which enhances various physical and chemical processes near the surface, e.g., Raman scattering or fluorescence intensities of molecules, [1][2][3][4] photoconversion efficiency of solar cell, [5,6] and yield of photochemical reactions. [7,8] Enhanced fluorescence intensity is termed surface-enhanced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 34 publications
2
47
1
Order By: Relevance
“…Interestingly, the size of ∼200 nm is in good agreement with that predicted by Mie scattering for a spherical Si particle producing the highest efficiency, as shown in Figure m. According to Mie scattering theory, the value of Q sca is proportional to the square of the electric field of the scattered light, corresponding to the magnitude of EF Figure e.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, the size of ∼200 nm is in good agreement with that predicted by Mie scattering for a spherical Si particle producing the highest efficiency, as shown in Figure m. According to Mie scattering theory, the value of Q sca is proportional to the square of the electric field of the scattered light, corresponding to the magnitude of EF Figure e.…”
Section: Resultssupporting
confidence: 76%
“…An objective lens (SMLPLN, 100×, Olympus) with a long working distance was used to obtain the spectrum for the CV solution under a cover glass. The optical cell for collection of the spectrum was designed to provide a solution layer between the cover glass and the Si powder. The EF values associated with the fluorescence intensities were obtained by acquiring four spectra, wherein the enhanced spectrum of the CV was divided by the spectrum of the CV, both of which had the background signals subtracted, as described in our reports previously. Fluorescence mapping measurements were conducted by collecting CV spectra with the same instrument and by scanning the sample in the cell on an x–y translation stage, as described in our report previously. ,, The grid size of the mapping data was due to the scan step of the stage, which was set to 500 nm, and the data collection time of the spectrum was 1 s. Using the mapping data, EFs were obtained and layered over the SEM image of the same sample.…”
Section: Methodsmentioning
confidence: 99%
“…It was recently reported that nanostructured TiO 2 can enhance the E-field intensity of the incident light with a factor of 10 3 −10 4 . 43,44 On the other hand, we never detected any sign of trapping using 370 nm light from a Hg lamp for a flat (mirror-polished) TiO 2 crystal. This indicates that such enhancement effects strongly assist the laser-free optical trapping phenomenon observed here.…”
Section: Discussionmentioning
confidence: 61%
“…57 For example, using this method, it was found that the TiO2 porous layer gives many hot spots with significantly high electric fields. 58 This electric field enhancement effect of the nanostructured TiO2 enables surface-enhanced Raman spectroscopic (SERS) detection of adsorbed molecules. 59 Fig.…”
Section: Fdtd Calculations Of Electric Field Distributionsmentioning
confidence: 99%